Reevaluation of the 11 november 1858 earthquake and tsunami in Setubal: a contribution to the seismic and tsunami hazard assessment in Southwest Iberia - Wronna, Martin (2022)
The southwest Iberian Margin (SWIM) hosted a series of tsunamigenic earthquakes. However, strong magnitude earthquakes M > 7.0 are scarce and geological and geophysical evidence suggest that slow deformation occurs on a large area without a discrete plate boundary. The reanalysis of this event is crucial because of its location in a possible transition zone between the diffuse plate boundary and the stable continent regime. The 11 November 1858 earthquake in Setubal, Portugal, with an estimated M similar to 7, ruined a large part of the city and was felt all over Portugal and large parts of the Iberian Peninsula. Earlier studies suggest an epicentre close to the shore, less than 50 km away, and there exists a description of a tsunami in Setubal. We use macroseismic intensities and present a reevaluation of the event parameters: depth, epicentre, magnitude, and fault orientation. We select the candidate faults according to the epicentral area and plate kinematics and use scaling laws for the magnitude range. We use tsunami numerical modelling to check the tsunamigenic potential of the event. Finally, we compute the tsunami propagation and inundation for Setubal for seven candidate scenarios and analyze waveform data obtained at virtual tide gauges. Our results favour an offshore inverse fault compatible with the tsunami observation corresponding to a reverse fault with a 40 degrees strike angle at 13 km depth and a magnitude range of 6.8 +/- 0.3.